2022
DOI: 10.1039/d1an02188e
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin detection at ppt level in human saliva by an extended-gate-type organic field-effect transistor

Abstract: Herein, we report an extended-gate-type organic field-effect transistor (OFET) sensor for oxytocin. The fabricated OFET-based immunosensor has successfully detected oxytocin at ppt levels in human saliva with high recovery rates...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 48 publications
(54 reference statements)
0
10
0
Order By: Relevance
“…Saliva is an important and reliable non-invasive test [ 158 , 169 ]. An extended-gate-type OFET sensor was reported for oxytocin.…”
Section: Applications Of the Flexible Ofets-based Sensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Saliva is an important and reliable non-invasive test [ 158 , 169 ]. An extended-gate-type OFET sensor was reported for oxytocin.…”
Section: Applications Of the Flexible Ofets-based Sensorsmentioning
confidence: 99%
“…An extended-gate-type OFET sensor was reported for oxytocin. The fabricated OFET-based immunosensor has successfully detected oxytocin at a ppt level in human saliva with high recovery rates (96–102%) [ 158 ].…”
Section: Applications Of the Flexible Ofets-based Sensorsmentioning
confidence: 99%
“…[43] The approach to control the orientation of recognition scaffolds on the electrode was applied to the selective detection of a hormone showing a complicated chemical structure in human saliva using an extended-gate-type OFET. [46] The target oxytocin comprising nine amino acid residues plays an important role in biological systems as a neurotransmitter. [47] Significant roles of oxytocin including an age-specific circulating hormone, [48] an anabolic bone hormone, [49] and medicine for chronic abdominal pain in peripheral tissue [50] have been reported, indicating that oxytocin is an essential biomarker.…”
Section: Selective Detection Using Ofet-based Immunoassaymentioning
confidence: 99%
“…c) Spike-and-recovery test for oxytocin in the human saliva sample. Reproduced with permission [46]. Copyright 2022, The Royal Society of Chemistry.…”
mentioning
confidence: 99%
“…Rather than the above-revisited nanostructures in organic materials, efforts to perform structural engineering at a device level were also made. In 2022, Minami et al reported oxytocin detection at pg·mL −1 (part per trillion level) using an extended-gate structure with OFETs [ 66 ]. An anti-oxytocin antibody-attached self-assembled monolayer (SAM) was used in their devices; modified streptavidin on SAM was applied to immobilize biotinylated anti-oxytocin antibodies via biotin-avidin interaction.…”
Section: Device Structurementioning
confidence: 99%